O jo, nu'ca menibat? suglung at iamut deng piling amanung Capampangan - Osmubal Papa ([Angeles City, Philippines] Juan D. Nepomuceno Center for Kapampangan Studies, Holy Angel University, 2011)
On the etymology of Kapampangan words and phrases.
In Pampanga.
Keywords: Pampanga language -- Etymology